The Lab Book : Situated Practices in Media Studies - Wershler-Henry, Darren S. (Darren Sean), 1966-; Parikka, Jussi, 1976-; Emerson, Lori (Book collections on Project MUSE., 2021)
"An important new approach to the study of laboratories, presenting a practical method for understanding labs in all walks of life"--